2022
DOI: 10.1007/s13205-022-03221-3
|View full text |Cite
|
Sign up to set email alerts
|

A highly sensitive wearable pressure sensor capsule based on PVA/Mxene composite gel

Abstract: Wearable sensors have drawn considerable interest in the recent research world. However, simultaneously realizing high sensitivity and wide detection limits under changing surrounding environment conditions remains challenging. In the present study, we report a wearable piezoresistive pressure sensor capsule that can detect pulse rate and human motion. The capsule includes a flexible silicon cover and is filled with different PVA/MXene (PVA-Mx) composites by varying the weight percentage of MXene in the polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Both PVA 15 /CD/HAG and PVA 15 /CD/HAG/ CD AgNP spectra exhibit a major peak at 19° (2θ) corresponding to PVA. [ 65 ] PVA 15 /CD/HAG/ CD AgNP generated two additional peaks at 38° and 44° attributed to the (111) and (200) diffracting planes of Ag, respectively. [ 66 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both PVA 15 /CD/HAG and PVA 15 /CD/HAG/ CD AgNP spectra exhibit a major peak at 19° (2θ) corresponding to PVA. [ 65 ] PVA 15 /CD/HAG/ CD AgNP generated two additional peaks at 38° and 44° attributed to the (111) and (200) diffracting planes of Ag, respectively. [ 66 ]…”
Section: Resultsmentioning
confidence: 99%
“…Both PVA 15 /CD/HAG and PVA 15 /CD/HAG/ CD AgNP spectra exhibit a major peak at 19°( 2𝜃) corresponding to PVA. [65] PVA 15 /CD/HAG/ CD AgNP generated two additional peaks at 38°and 44°attributed to the (111) and ( 200) diffracting planes of Ag, respectively. [66] SEM was employed to examine the surface structure of PVA 5-20 /CD/HAG and PVA 15 /CD/HAG/ CD AgNP (Figure 1c,d; Figure S5, Supporting Information).…”
Section: The Assembling Of Pva/cd/hag/ CD Agnpmentioning
confidence: 99%
“…The sensitivity value of our sensor exceeded several sensors and is much more sensitive than the reported PET/MXene film. The response times are also competitive [ 39 , 40 , 41 , 42 ]. Moreover, the minimum pressure value of 60 Pa is much lower than other flexible sensing materials.…”
Section: Resultsmentioning
confidence: 99%
“…Kallingal et al reported a wearable piezoresistive pressure sensor capsule that can detect pulse rate and human motion. [120] The capsule includes a flexible silicone cover and is filled with different PVA/MXene composite materials by changing the weight percentage of MXene in the polymer matrix. The sensor capsule based on PVA/MXene gel significantly gives a low detection limit of 2 kPa, shows a high sensitivity of 0.45 kPa −1 in the range of 2-10 kPa, shows a response time of about 500 ms, and has good mechanical stability and non-fading durability of 500 cycles.…”
Section: Other Gel Materialsmentioning
confidence: 99%